2010
DOI: 10.1111/j.1540-8167.2009.01612.x
|View full text |Cite
|
Sign up to set email alerts
|

Septal Dyskinesia and Global Left Ventricular Dysfunction in Pediatric Wolff‐Parkinson‐White Syndrome with Septal Accessory Pathway

Abstract: The dyskinetic segment activated by a right septal AP in WPW syndrome may lead to ventricular dilation and dysfunction. RFA produced mechanical resynchronization, reverse remodeling, and improvements in LV function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
1
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 22 publications
6
82
1
4
Order By: Relevance
“…A previous report showed that LV dyssynchrony induces low cardiac output which leads to cardiac failure in some cases. 15) However, in our case, the cause of the high levels of BNP might be LV hypertrophy and the high value of LV pressure overload. Carvedilol and cibenzoline were effective for reduction of BNP levels due to relief of the LVOT pressure gradient.…”
Section: Discussionmentioning
confidence: 88%
“…A previous report showed that LV dyssynchrony induces low cardiac output which leads to cardiac failure in some cases. 15) However, in our case, the cause of the high levels of BNP might be LV hypertrophy and the high value of LV pressure overload. Carvedilol and cibenzoline were effective for reduction of BNP levels due to relief of the LVOT pressure gradient.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, the abnormal septal motion associated with this contractile pattern is more frequently found in patients with a prolonged QRS duration in both WPW 8,12 and LBBB patients. 11 In patients with an LBBB and heart failure receiving CRT, this classical LBBB longitudinal strain pattern has been linked to the occurrence of LV reverse remodeling, improvement in LV function, and clinical outcome, even in patients with relatively narrow QRS (120-150 ms) in whom the benefit of CRT remains uncertain.…”
Section: Wpw Syndrome Septal Preexcitation Dyssynchrony and Cardiamentioning
confidence: 99%
“…7 Reduced IVS motion and LV dyssynchrony associated with septal AP may result in LV dysfunction, which resolves after radiofrequency ablation, even in the absence of permanent tachycardia. 8,9 In both septal AP ( Figure A) and LBBB ( Figure D), activation proceeds across the septum at the breakthrough point before reaching the LV endocardium. It then slowly propagates to the endocardium of the posterolateral wall, with a basal breakthrough site in the event of an AP and more often a mid to apical septal one in the event of an LBBB.…”
Section: Wpw Syndrome Septal Preexcitation Dyssynchrony and Cardiamentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Recently, an accessory pathway has been reported to contribute to LV septal dyskinesia and LV dysfunction in the absence of documented SVT. [7][8][9][10][11] Many patients exhibit right septal or posteropesptal accessory pathways. Herein, we report a case of WPW syndrome with right-sided free-wall accessory pathway and LV dysfunction.…”
Section: Introductionmentioning
confidence: 99%